Performance improvement of a triple-junction GaAs-based solar cell using a SiO 2 -nanopillar/SiO 2 / TiO 2 graded-index antireflection coating. (17th March 2014) - Liu, Jheng-Jie; Ho, Wen-Jeng; Syu, Jhih-Kai; Lee, Yi-Yu; Lin, Ching-Fuh; Shiao, Hung-Pin
In this study, the enhanced performance of a triple-junction GaAs-based solar cell using a SiO2 -nanopillar/SiO2 /TiO2 graded-index antireflection coating (GI-ARC) was demonstrated. The optical reflectance, photovoltaic current-voltage (I-V), and external quantum efficiency (EQE) of a cell with a SiO2 /TiO2 double-layer (DL) ARC and a cell with a GI-ARC were measured and compared. The cell with a GI-ARC exhibited the lowest optical reflectance. Thus, the average EQE enhancements (ΔEQE) of the cell with a GI-ARC compared to the cell with a DL-ARC were 5.88% for the top cell and –1.56% for the middle cell. In addition, a small difference in the photocurrent generated between the top cell and the middle cell was achieved. Finally, an additional 0.52% increase (from 24.99% to 25.51%) in conversion efficiency was obtained.